Rancang Bangun dan Analisis Shutter Conveyor Reversible Semi–Otomatis Berbasis PLC Guna Mengurangi Waktu Proses Material Handling Pada Line Assembly Steering Tipe D74 di PT. Akashi Wahana Indonesia - Supandi Supandi; Wahyu Isti Nugroho; Iswanocta Candra Yudhistira (Politeknik Negeri Semarang, 2023)
PT Akashi Wahana Indonesia is an automotive manufacturer that specializes in producing steering gear assemblies. The steering gear assembly process involves assembling the components of the steering gear into a single unit. A problem related to cycle time has been identified at a process position on the D74 steering gear assembly line. The cause of this issue is the manual shutter used to transfer assembly results between process positions, which requires manual intervention by operators, resulting in non-value-added time and unnecessary movement. The proposed solution to this problem is to design and development a PLC based semi-automatic reversible shutter conveyor. This shutter conveyor will serve as a material handling tool to change the transfer system between process positions. Operators can initiate the transfer to the next position by simply pressing the start button. The research methodology encompasses problem identification, literature review, design, production, and testing. The analysis includes calculations of stress and strain on the base slider, and percentage comparisons of material handling process time before and after improvement. Testing will be conducted through experiments on material handling process time. The result of this research is the implementation of a PLC-based semi-automatic reversible shutter conveyor in the D74 steering assembly line, which has achieved a 69.1% reduction in material handling process time.